1996
DOI: 10.1006/viro.1996.0223
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Bovine Herpesvirus-1 (BHV-1) Glycoprotein gL Which Is Required for Proper Antigenicity, Processing, and Transport of BHV-1 Glycoprotein gH

Abstract: DNA sequence analysis of the bovine herpesvirus-1 (BHV-1) genome revealed the presence of an open reading frame named UL1 which exhibited limited homology to glycoprotein gL of herpes simplex virus-1 (S. K. Khattar, S. van Drunen Littel-van den Hurk, L. A. Babiuk, and S. K. Tikoo, Virology 213, 28-37). To identify the BHV-1 UL1 protein, rabbit antisera were prepared against two synthetic peptides that were predicted by computer analysis to encompass antigenic epitopes. Sera against both peptides immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Glycoprotein H (gH) is highly conserved among human and animal herpesviruses (McGeoch & Davison, 1986 ;Keller et al, 1987 ;Gompels et al, 1988 ;Pachl et al, 1989 ;Josephs et al, 1991 ;Klupp & Mettenleiter, 1991 ;Xu et al, 1992 ;Maeda et al, 1993 ;Scott et al, 1993 ;Mukai et al, 1997 ;Pepper et al, 1996). It functions in the penetration step and in cell-to-cell spread, but not in the attachment step (Keller et al, 1987 ;Forrester et al, 1992 ;Peeters et al, 1992 ;Wilson et al, 1994 ;van Drunen Littel-van den Hurk et al, 1996 ;Babic et al, 1996). In addition, gH elicits antibodies which can neutralize Author for correspondence : Koichi Yamanishi.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycoprotein H (gH) is highly conserved among human and animal herpesviruses (McGeoch & Davison, 1986 ;Keller et al, 1987 ;Gompels et al, 1988 ;Pachl et al, 1989 ;Josephs et al, 1991 ;Klupp & Mettenleiter, 1991 ;Xu et al, 1992 ;Maeda et al, 1993 ;Scott et al, 1993 ;Mukai et al, 1997 ;Pepper et al, 1996). It functions in the penetration step and in cell-to-cell spread, but not in the attachment step (Keller et al, 1987 ;Forrester et al, 1992 ;Peeters et al, 1992 ;Wilson et al, 1994 ;van Drunen Littel-van den Hurk et al, 1996 ;Babic et al, 1996). In addition, gH elicits antibodies which can neutralize Author for correspondence : Koichi Yamanishi.…”
Section: Introductionmentioning
confidence: 99%
“…infectivity in the absence of complement and is thus a target of the host immune response (Ghiasi et al, 1992 ;Liu et al, 1993 b ;Qian et al, 1993 ;Rapp et al, 1994 ;Khattar et al, 1996 ;Urban et al, 1996 ;Nemeckova et al, 1996). It also forms a complex with a smaller glycoprotein, glycoprotein L (gL), which is required for normal processing and transport of gH to the cell membrane and thus acts as a molecular chaperone (Hutchinson et al, 1992 ;Kaye et al, 1992 ;Klupp et al, 1994 ;Pulford et al, 1995 ;Duus et al, 1995 ;Duus & Grose, 1996 ;Khattar et al, 1996 ;Mukai et al, 1997 ;Stokes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BHV-1 gH forms a complex with another glycoprotein, gL, which is necessary for the proper processing and transport of gH but not gL (Khattar et al, 1996). In addition, the BHV-1 gH-gL complex is required for induction of a neutralizing antibody response and anchoring of gL to the plasma membrane (Khattar et al, 1996).…”
mentioning
confidence: 99%
“…BHV-1 gH forms a complex with another glycoprotein, gL, which is necessary for the proper processing and transport of gH but not gL (Khattar et al, 1996). In addition, the BHV-1 gH-gL complex is required for induction of a neutralizing antibody response and anchoring of gL to the plasma membrane (Khattar et al, 1996). Characterization of PrV and HSV-1 gH null mutants has indicated that gH of these viruses is an essential glycoprotein which is involved in both fusion between virion and cellular membranes during virus entry and in cell-to-cell spread of the virus (Forrester et al, 1992 ;Babic et al, 1996).…”
mentioning
confidence: 99%